Study on The Potentially Harmful Benthic Dinoflagellates in Pari Island, Indonesia - Hikmah Thoha; Arief Rachman; Mariana Destiana Bayu Intan; Gires Usup (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Information on benthic dinoflagellates in Indonesia is rare since it often neglected in many microalgae researches. Thus, not much information is available about the ecology of benthic dinoflagellates in Indonesia, especially for three important genus, Gambierdiscus, Prorocentrum and Ostreopsis. Sampling were carried three times: in August, October, and December 2013. The sampling was conducted around Pari Island. Bethic Harmful Algal Blooms (B-HABs) were collected in each sampling site using a modified PVC rig with 15x10 cm screen (artificial substrate) which placed at the bottom of the water for 24 hours. Another form of a screen with leaf blade form, 30x5 cm was also deployed in each sampling site and left for 24 hours. In general, the different density of Prorocentrum, Gambierdiscus, and Ostreopsis were observed in various substrates in this research. Temporal variation of those three target genera was also found in this research, from the results so far, Prorocentrum was suggested as the most common benthic dinoflagellates in Pari Island. This genus was found in all substrates during two sampling periods in this study, except in sandy bottom substrate in October 2013. The highest density of Prorocentrum which observed in the screen placed in coral reefs area in October 2013, was 288 cells/100 cm2. The lowest of Prorocentrum density was observed in coral reefs area in October 2013, was 0.53 cells/g of wet weight.